Autotrophic and Heterotrophic Metabolism of Hydrogenomonas: Regulation of Autotrophic Growth by Organic Substrates - Stukus, Philip E. (1970)
The effects of a number of organic substrates on the autotrophic metabolism of Hydrogenomonas eutropha were examined. Dual substrate (mixotrophic) cultivation in the presence of hydrogen plus either fructose or alanine allowed autotrophic growth to begin immediately after the exhaustion of the organic substrate. On the other hand, the presence of acetate, pyruvate, or glutamate caused a lengthy lag to occur before autotrophic growth commenced. With acetate or pyruvate this lag (plateau) in the dicyclic growth curve was due to the repression of ribulose diphosphate carboxylase (RDPC) synthesis during mixotrophic growth. During heterotrophic growth with glutamate, RDPC was partially repressed; however, during mixotrophic growth, RDPC activity was high. Thus the delay of autotrophic growth was not due to a repression of RDPC by glutamate. The data suggest that glutamate interferes with autotrophic metabolism by repressing the incorporation of inorganic nitrogen. The repression of these vital autotrophic functions by acetate, pyruvate, and glutamate occurred both in the presence and absence of hydrogen, i.e., during both heterotrophic and mixotrophic cultivation. The derepression of the affected systems during the plateau phase of the dicyclic growth curves was demonstrated. Carbon dioxide assimilation by whole cells agreed well with the RDPC activity of extracts from cells grown under similar conditions.